2018
DOI: 10.15517/rbt.v66i3.31035
|View full text |Cite
|
Sign up to set email alerts
|

Intra and inter annual variation in a seagrass meadow on the Caribbean coast of Costa Rica: 2009-2015

Abstract: Seagrass beds are an important ecosystem on the Caribbean coast of Costa Rica. At Cahuita National Park (CNP) a seagrass bed at Perezoso has been monitored continually since 1999 within the CARICOMP program. Thalassia testudinum is the dominant seagrass species, in some cases mixed with Syringodium filiforme. The results from the 2009 to 2015 monitoring period are presented here, and contrasted with data before 2009. Total (above and below ground tissue) mean biomass of T. testudinum was higher (1 255.4 ± 146.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 14 publications
0
11
0
3
Order By: Relevance
“…In the Caribbean coast of Costa Rica there are six seagrass species and the most extensive meadows are found in Cahuita and Manzanillo (Samper-Villarreal et al 2018 (Fonseca et al 2007;Cortés et al 2010;Loría-Naranjo et al 2018). At the time of this study, Syringodium filiforme grew in these meadows in dense mono-specific patches (Fig.…”
Section: Study Areamentioning
confidence: 74%
See 2 more Smart Citations
“…In the Caribbean coast of Costa Rica there are six seagrass species and the most extensive meadows are found in Cahuita and Manzanillo (Samper-Villarreal et al 2018 (Fonseca et al 2007;Cortés et al 2010;Loría-Naranjo et al 2018). At the time of this study, Syringodium filiforme grew in these meadows in dense mono-specific patches (Fig.…”
Section: Study Areamentioning
confidence: 74%
“…There was no variability in S. filiforme shoot length between the months surveyed, in contrast with the seasonality found in other parts of the Caribbean. Seasonal variation in leaf dynamics (Barber & Behrens, 1985;Fry & Virnstein, 1988;Short et al 1993) andbiomass (Van Tussenbroek, 1994) (Loría-Naranjo et al 2018), with biomass and productivity reported to decrease at higher temperatures (Cortés et al 2010). The reasons for a lack of variation in S. filiforme shoot length during our study remain unclear, and potential confounding factors such as grazing dynamics (Valentine & Duffy, 2006) should be assessed at this study site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dicho monitoreo se ha llevado a cabo utilizando la metodología del Programa de Productividad Costera y Marina del Caribe (CARICOMP), el cual hace mediciones de densidad, área foliar, productividad y biomasa de los pastos marinos en el Parque Nacional Cahuita. Los datos de dicho monitoreo se han analizado estadísticamente y los resultados se han publicado en múltiples artículos científicos (Fonseca, Nielsen & Cortés, 2007;Cortés et al, 2010;Loría-Naranjo et al, 2018).…”
Section: Pastos Marinos En Costa Ricaunclassified
“…En el Caribe Sur ha aumentado la presión sobre los hábitats de los arrecifes de coral debido al aumento de la sedimentación, principalmente vinculado a las prácticas agrícolas extensivas de banano y piña para exportación (Cortés y Risk, 1985;Cortés et al, 2010a). Las praderas de pastos marinos han presentado períodos de estabilidad y cambios a lo largo de los años (Cortés, 2010a;Van Tussenbroek et al, 2014;Loría-Naranjo et al, 2018). Los ecosistemas de manglar en el Caribe de costa Rica representan únicamente el 1% del total del país, y están concen-trados casi exclusivamente en el manglar de Gandoca en el Caribe Sur.…”
Section: Estado De Los Ambientes Marinos Y Costerosunclassified